Building and codifying visual abilities tests for female students of the College of Physical Education and Sports Sciences for Girls - Abaas , Warda Ali; Nayyef, Sahar Amer (International Journal of Psychosocial Rehabilitation, 2020)
The field of physical education has recently witnessed development in sports activities as a result of studies and research carried out by many researchers, including studies on testing and measurement, as the field of tests in physical education and sports science has many horizons that extend to the fields of teaching, training and auxiliary sciences. It targets the athlete's category, whether they are within the categories of players or students of colleges of physical education and of all ages, as the tests are an essential part in the plan to improve physical and skilful performance. On the results of studies and research that take the test as a tool used for the purpose of reaching a solution to the presented problems,In light of that comprehensiveness and multiplicity of the extension of these horizons by imposing the principle of specialization in the test must be adhered to in order to achieve the demands or goals of applying the tests. The field of physical education and sport science includes many sports activities that require many capabilities, including visual abilities, which is one of the capabilities that research and studies have proven its impact and effectiveness on skill performance. As the eye has a set of basic functions through which we can collect information about our surroundings, Since we can distinguish visual images, whether static or moving, the visual ability is the ability to receive visual stimuli, interpret and perceive them, and translate what has been visually perceived into movement or a group of kinetic forms.From here came the importance of research in building and codifying tests for static and mobile visual capabilities and perception of horizontal depth, as these tests are an objective tool for measuring students' visual capabilities that enable specialists to diagnose the strengths and weaknesses of the student's visual ability and thus be able to address weakness and strengthen strengths, which positively affects The student's skill performance. As for the research problem, the two researchers were able, through reviewing scientific sources and references and previous studies, to arrive at the absence of tests for the visual abilities of the students of the College of Physical Education and Sports Science for Girls, and this situation indicates an existing problem for which appropriate solutions must be developed. Physical education and sports sciences for girls and placing them in front of specialists to use them in measuring the visual abilities and determining their levels of female students of the College of Physical Education and Sports Sciences.